Peran Guru Pendidikan Agama Islam Dalam Mengembangkan Pendidikan Multikultural - Huda, Mualimul (Jurnal Kajian Pendidikan Islam, 2022)
The crisis that has penetrated Indonesia now is a multidimensional crisis, starting from a crisis of morality, ethics and tolerance. The decline in moral values ​​in students has now become a challenge and warning for all parties, especially educational institutions, the role of teachers and parents. Many cases happen to young people, ranging from cases of intolerance, bullying, promiscuity and other deviant acts. Various multidimensional crises in Indonesia, whether recognized or not are part of the cultural problems one of the causes is the diversity of cultures that exist in our society. Cultural diversity should not be a cause of discrimination, injustice, suspicion and various human rights violations, but rather a force to build togetherness. The teacher has an important role in the transmission of science, information, character education, research, recreation, and cultural understanding. The thought of multicultural Islamic education in Indonesia is based on Islamic teachings as a source of thought. Multiculturality is a sunnatullah that can not be avoided in it contains important values ​​for the development of faith and social life the role of the teacher plays an important role in rectifying the understanding of Islam that deviates from the understanding of Islam which is "Rahmatan lil allamin". This study includes the study of library research using an empirical-based qualitative approach. In this study the study of literature was used in collecting data. While the data analysis technique uses content analysis by sorting the data then grouping similar data and then analyzing the contents according to the purpose of the study. The result is that it takes the role and role model of the teacher about mutual respect by acting fairly, objectively, giving feedback and reflection in learning , use polite language and not touch sensitive issues related to religious and ethnic differences. The need to emphasize multicultural values ​​in the curriculum of Islamic religious education, and integrate teaching models and methods so that learning objectives can be achieved. The development of multicultural Islamic education is felt to be able to become a means in building a more substantive, contextual, positive and constructive national civilization. It is hoped that teachers will be able to encourage students to have awareness and understanding to always uphold the values ​​of justice, democracy, humanity and pluralism in relationships.